Identification of Occupational Health and Safety's Hazards in Formwork Fabrication Area of Building Construction Project - Zulhayudin, Muhammad Fadillah; Razzak, Abdul (Periodicals of Occupational Safety and Health, 2024)
Background: Potential hazards are a threat to the safety and health of workers. Formwork fabrication as a woodworking area to create molds that will be used for the casting process of columns, beams and plates is not spared from potential hazards. Initial observations reveal some potential hazards that are of interest to be further identified. This study aims to identify potential hazards in the formwork fabrication area. The benefit is that it can be the basis for assessing risk and determining appropriate control determinants; Method: This type of research is a descriptive survey with an observational approach. The method used is a Walkthrough Survey with a hazard identification sheet instrument. Hazard identification is carried out based on UURI Number 1 of 1970 and PPRI Number 50 of 2012, namely identifying potential hazards sourced from humans, production materials, equipment, machinery, working methods and work environment; Results: Unsafe action; The use of materials that are large, heavy and have sharp edges; The use of hammers, saws, rotation of grinding blades, sparks, use of electrical connectors is not feasible; Works without structured flows and procedures; Vibration, noise, heat pressure, dust, fecal coliform, mosquitoes, centipedes, unstructured workstation layout, awkward posture, manual handling, and repetitive body movements are some of the potential hazards that have been successfully identified; and Conclusion: Each potential hazard has its own risk that has not been assessed in this study. Likewise, the determinants of its control have not been included in this study. For this reason, further research is needed to assess risks and determine control determinants based on the potential hazards that have been identified in this study.